Comparison Of Operative Outcomes of Open Versus Percutaneous Pedicle Screw Fixation for the Treatment of Lumbar Spondylolisthesis: Operative Outcomes of Open vs Percutaneous Pedicle Screw Fixation in Lumbar Spondylolisthesis - Shahid, Subhan; Falak, Salman; Shafique, Danish; Abbas, Talha; Ahmad, Murtaza; Hameed, Abdul; Lodhi, Fahad Aftab Khan (Pakistan Journal of Health Sciences, 2026)
Lumbar spondylolisthesis often requires surgical correction, with options like open or percutaneous pedicle screw fixation. Objectives: To compare their outcomes, focusing on reduced trauma, blood loss, and postoperative pain with the percutaneous approach. Methods: A quasi-experimental trial at Sir Ganga Ram Hospital, Lahore, included 44 patients with lumbar spondylolisthesis. Exclusion criteria were metabolic bone diseases, prior spine surgery, pregnancy, and spinal malignancy. Patients were divided into Group A (percutaneous fixation) and Group B (open Pedicle screw fixation). Intraoperative time, blood loss, and VAS pain scores were recorded. The outcome variables were postoperative hospital stay, blood loss, and surgery duration. Data was analyzed by using SPSS 25.0. Results: Among 44 participants, 20 were male, and 24 were female. Group A had 6 males (27.3%) and 16 females (72.7%), while Group B had 14 males (63.6%) and 8 females (36.4%). Mean intraoperative time was 44.45 ± 6.87 minutes in Group A vs. 51.27 ± 3.45 in Group B. Blood loss was significantly lower in Group A (52.82 ± 3.45 mL) compared to Group B (349.23 ± 92 mL, p<0.05). Postoperative pain at 6 weeks (Group A: 3.09 ± 1.41 vs. Group B: 3.36 ± 1.59) and 3 months (Group A: 2.18 ± 1.09 vs. Group B: 2.0 ± 1.02), indicating no statistical difference. Conclusions: Compared with traditional posterior muscle stripping treatments, percutaneous pedicle screw fixation proves an effective treatment in terms of less postoperative blood loss and operative time. This highlights the technique’s potential advantages in improving patient recovery without compromising long-term pain outcomes.